Interaction ritual : essays on face-to-face behavior - Goffman, Erving (New York : Pantheon Books, 1967)
From the exemplary opening essay of Interaction Ritual, “On Face-Work,” —a full account of the extraordinary repertoire of maneuvers we employ in social encounters in order to “save face”—to the final, and classic, essay “Where the Action Is,”—an examination of people in risky occupations and situations: gamblers, criminals, coal miners, stock speculators—Goffman astounds us with the unexpected richness and complexity of brief encounters between people. For Goffman, as for Freud, the extreme cases are of interest because of the light they shed on the normal: The study of the trapeze artist is worthwhile because each of us is on the wire from time to time.
Bibliografija uz tekst
Keywords: etnometodologija; društvena interakcija; "face-to-face" ponašanje